(untitled) (Педагогіка вищої та середньої школи, 2003)
The article deals with the methods of control and registration of pupils’ knowledge in the twenties of the last century. Our research has led us to the conclusion that the new system of methods of control and registration of pupils knowledge was being formed at the time in the Ukrainian school. It united both methods of individual and mass control of pupils’ knowledge. Special emphasis was made on the methods of control of orthographic ally habits and skills because the problem of literacy of the population of Ukraine (both schoolchildren and grown-ups) was very urgent.